2015
DOI: 10.1073/pnas.1516401112
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of the tryptophan synthase β-subunit for stand-alone function recapitulates allosteric activation

Abstract: Enzymes in heteromeric, allosterically regulated complexes catalyze a rich array of chemical reactions. Separating the subunits of such complexes, however, often severely attenuates their catalytic activities, because they can no longer be activated by their protein partners. We used directed evolution to explore allosteric regulation as a source of latent catalytic potential using the β-subunit of tryptophan synthase from Pyrococcus furiosus (PfTrpB). As part of its native αββα complex, TrpB efficiently produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
264
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 146 publications
(279 citation statements)
references
References 51 publications
13
264
0
2
Order By: Relevance
“…The spectrum of AfTrpB 0B2 , on the other hand, is almost identical to that of AfTrpS, with a prominent λ max of 350 nm ( Figure 2c). This behavior matches what we observed previously [3] and provides compelling evidence that the 0B2 mutations activate AfTrpB by the same mechanism as they did in PfTrpB, namely by mimicking the allosteric activation produced by binding of TrpA to TrpB.…”
Section: Introductionsupporting
confidence: 90%
“…The spectrum of AfTrpB 0B2 , on the other hand, is almost identical to that of AfTrpS, with a prominent λ max of 350 nm ( Figure 2c). This behavior matches what we observed previously [3] and provides compelling evidence that the 0B2 mutations activate AfTrpB by the same mechanism as they did in PfTrpB, namely by mimicking the allosteric activation produced by binding of TrpA to TrpB.…”
Section: Introductionsupporting
confidence: 90%
“…[23] Screening made use of starting materials containing a mixture of diastereomers, however only the (2S,3R) diastereomer underwent a productive reaction. High-throughput screening of 352 variants yielded PfTrpB 0E3 (L91P), which displayed a 43-fold increase in TTN for β-EtTrp (Figure 4d).…”
Section: We Chose Pftrpbmentioning
confidence: 99%
“…Recombination also included F274L, which was previously identified as an activating mutation. [23] Recombined variants were assayed for β-EtTrp production at 290 nm, which revealed that I68V and T321A were non-essential, but that F274L was beneficial, yielding variant PfTrpB 7E6 . Though PfTrpB 7E6 did not show improved stability (Table S2), recombination did enhance activity, with a 58-fold improvement relative to PfTrpB 2B9 (Figure 4d).…”
Section: B9mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we used directed evolution to engineer TrpB from Pyrococcus furiosus ( Pf TrpB) to retain activity in the absence of its TrpA partner. 5 We then further engineered this stand-alone enzyme to catalyze the efficient β-substitution of L-threonine (Thr), yielding (2 S ,3 S )-β-methyltryptophan (β-MeTrp) in a single step. 6 This non-canonical amino acid is an intermediate in the biosynthesis of maremycin and streptonigrin, and is natively produced from Trp through a three-enzyme, four-step pathway.…”
mentioning
confidence: 99%